2000
DOI: 10.1021/bi002499f
|View full text |Cite
|
Sign up to set email alerts
|

Transition State Structure of Purine Nucleoside Phosphorylase and Principles of Atomic Motion in Enzymatic Catalysis,

Abstract: Immucillin-H [ImmH; (1S)-1-(9-deazahypoxanthin-9-yl)-1,4-dideoxy-1,4-imino-D-ribitol] is a 23 pM inhibitor of bovine purine nucleoside phosphorylase (PNP) specifically designed as a transition state mimic [Miles, R. W., Tyler, P. C., Furneaux, R. H., Bagdassarian, C. K., and Schramm, V. L. (1998) Biochemistry 37, 8615-8621]. Cocrystals of PNP and the inhibitor are used to provide structural information for each step through the reaction coordinate of PNP. The X-ray crystal structure of free ImmH was solved at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
265
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(285 citation statements)
references
References 29 publications
20
265
0
Order By: Relevance
“…For this scheme, assuming the chemical step is irreversible (i.e., k 4 and reverse commitment, C r = 0), the V/K KIE, symbolized as T (V/K), is related to the equilibrium BIE ( T K eq ) and the intrinsic KIE ( T k 3 ) by Equation 6 (46,47): (6) where T k 1 is the intrinsic KIE for binding and C f is the forward commitment to catalysis, defined as k 3 /k 2 . In cases where C f is low, the T k 1 C f term in Equation 6 can be approximated within experimental error as C f , 4 yielding Equation 7:…”
Section: Intrinsic Kinetic Isotope Effects From V/k Kinetic Isotope Ementioning
confidence: 99%
“…For this scheme, assuming the chemical step is irreversible (i.e., k 4 and reverse commitment, C r = 0), the V/K KIE, symbolized as T (V/K), is related to the equilibrium BIE ( T K eq ) and the intrinsic KIE ( T k 3 ) by Equation 6 (46,47): (6) where T k 1 is the intrinsic KIE for binding and C f is the forward commitment to catalysis, defined as k 3 /k 2 . In cases where C f is low, the T k 1 C f term in Equation 6 can be approximated within experimental error as C f , 4 yielding Equation 7:…”
Section: Intrinsic Kinetic Isotope Effects From V/k Kinetic Isotope Ementioning
confidence: 99%
“…In particular, the functional role of fast picosecond protein motions in catalysis and the dynamic nature of the transition state barrier crossing is a subject of ongoing and current debate (7)(8)(9)(10)(11)(12)(13). Theoretical studies have suggested that fast vibrations in enzymes might generate transition state conformations conducive to the chemical reaction (7,8,(14)(15)(16)(17)(18)(19)(20)(21), a familiar concept for reactions in ordinary solvents (22). In an alternative viewpoint, preorganization effects have been suggested to be a major contributing factor to enzyme catalysis (23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…Detailed analysis of the transition states for nucleoside phosphorylase (41) and OPRT (42) suggest that an important feature of the PRT mechanism is the concept of "nucleophillic displacement" (6). For nucleoside phosphorylase, this involves relatively fixed interactions to the nucleobase leaving group and Pi nucleophile, but a clear migration of C1′ (on the order 3 Å) from the leaving group to the Pi nucleophile.…”
Section: Implications For the Mechanism Of The Atp-prt Reactionmentioning
confidence: 99%